The new international financial architecture: Lessons and experiences from Africa (2019)
The purpose of this paper is to examine the requirements and successes of the New International Financial Architecture (NIFA) on transparency and corporate governance from a global perspective with a special focus on Africa. In recent years, transparency, accountability and governance have become key topics with many countries around the world having adopted International Financial Reporting Standards (IFRS) and corporate governance codes. The outcomes of these initiatives have been unconvincing. Desktop research was used to gather literature and data on compliance with corporate governance codes and International Financial Reporting Standards (IFRS) and other NIFA requirements. This study established that in spite of many regional and global initiatives by the World Bank and relevant regulators, compliance with IFRS and governance in parts of Africa has yet to reach its best level and guidelines are not fully followed leading to opportunities for improvement and policy adjustments. This research has implications and uses for both global and local institutions and regulators concerned with economic stability and growth including the World Bank, central banks, capital markets and boards of companies and the government in general. The findings contribute to governance debates by providing additional perspectives from Africa on compliance with accounting standards and codes in a region where research and corporate governance and reporting issues are still confusing.